2006
DOI: 10.1213/01.ane.0000194873.52453.bd
|View full text |Cite
|
Sign up to set email alerts
|

An Accuracy Evaluation of the T-Line® Tensymeter (Continuous Noninvasive Blood Pressure Management Device) versus Conventional Invasive Radial Artery Monitoring in Surgical Patients

Abstract: Continuous beat-to-beat arterial blood pressure (BP) monitoring with a simultaneous arterial waveform display is typically achieved with an invasive arterial catheter. We evaluated a noninvasive device, the T-Line Tensymeter, that provides a calibrated arterial pressure waveform from which continuous BP measurements and heart rate may be computed by either a bedside host monitor or the tensymeter device itself. In 25 patients given general anesthesia, we measured systolic, mean, and diastolic BPs via the tensy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 13 publications
4
39
0
Order By: Relevance
“…Our results are in concordance with recently published data from Janelle and colleagues [6], in which the blood pressure from the T-Line agreed with simultaneous contralateral blood pressures measured from arterial catheters over a systolic blood pressure range from 41 to 189 mmHg.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in concordance with recently published data from Janelle and colleagues [6], in which the blood pressure from the T-Line agreed with simultaneous contralateral blood pressures measured from arterial catheters over a systolic blood pressure range from 41 to 189 mmHg.…”
Section: Discussionsupporting
confidence: 93%
“…The T-Line utilises unique and proprietary signal processing algorithms to extract the physiologic arterial pressure waveform, without periodic external cuff recalibration. In a recent study, Janelle and colleagues [6] found that blood pressure readings using the T-Line agreed with simultaneous contralateral readings from arterial catheters within an acceptable clinical range in a limited population of surgical patients studied over a systolic arterial blood pressure range of 41-189 mmHg. It has been cleared for marketing by the Food and Drug Administration (USA) as a Class II medical device.…”
mentioning
confidence: 93%
“…It displays beat-to-beat radial artery pressure waveform with systolic, diastolic, mean BP and heart rate. Our present data confirms an earlier model TL-100 study that Tensys noninvasive beat-to-beat radial artery BP has a satisfactory level of agreement with an opposite radial artery A-Line over a wide range of blood pressure [4].…”
Section: Discussionsupporting
confidence: 91%
“…In an accuracy study on the predecessor TL-100 device during general anesthesia with a systolic BP range of 49-189 mm Hg, Janelle and Gravenstein showed an average 1.7 ± 7.0 (SD) mm Hg systolic BP difference (bias) between the TL-100 and contralateral radial A-Line, a 2.3 ± 6.9 mm Hg diastolic BP difference, and 1.7 ± 5.3 mm Hg mean BP difference [4]. Surgical studies with the TL-150 device in 21 subjects at 4 study sites demonstrated similar accuracy and reproducibility, including 6 diabetic patients with significant peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is unclear which technique the app is based on. Several articles have described methods for noninvasive continuous BP monitoring; however, it has been recognized that these methods are still prone to errors [48][49][50][51].…”
Section: Mobile Applicationsmentioning
confidence: 99%